The Experience of Emotional Distancing in the Management of Compulsive Hoarding: A Visual Methods Approach Using the “Hoard” Acronym Tool - Colin Jones; Satwant Singh (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Objective: Compulsive hoarding remains a significant public health issue, with many sufferers failing to acknowledge the problem. A number of methodological approaches have been utilised to explore and explain this complex phenomenon, though few have made use of contemporary visually inspired approaches. In an earlier study, it was found that visual methods proved beneficial in the research and subsequent treatment of compulsive hoarding, therefore a second study was designed with a specific focus on emotional distancing using the structured “HOARD” acronym tool. The findings of this study are presented in this paper.Method: Using a participatory visual action research approach a volunteer sample of 11 participants was recruited from a therapy group for sufferers of compulsive hoarding. Participants were asked to take photographs which best reflected their hoarding problem, and reflect upon these using the “HOARD” acronym tool whilst in a neutral environment and then again in their own home.Results: The experiences of participants were captured using semi-structured interviews, which were digitally recorded and later transcribed verbatim. Data were subject to rigorous qualitative analysis inspired by the Framework Technique.Conclusion: Emotional distancing occurs during these reflective activities, which seems to play an important role when utilising the “HOARD” acronym tool. Three key themes emerged from the data: The evocative power of the image, Images as monitoring tools and verifying and validating the hoarding problem.This particular methodological approach is beneficial in generating valuable narrative for self-reflection.